Service and Digital Marketing as Sustainability in MSMEs - Rahman, Iradah; Puji Handayati ,; Arief Noviarakhman Zagladi, (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
There are so many micro, small and medium enterprises in Indonesia. They are the backbone of Indonesia's economy. And petshop is an MSME that participates in coloring the Indonesian economy which is currently increasingly spreading. Small business owners may struggle to stay survive with a variety of conditions. Strategy is one of the keys to business success. And information technology is growing rapidly the last 10 years. So, the strategy must be collaborated with this information technology. To understand this, researchers investigated the strategy carried out by Alkautsar Petshop as a business in MSMEs, starting from its establishment to the present. The results show that a business needs to adapt to external and internal conditions in its business. This can be seen from the strategy used by petshop owners, by digital marketing and excellent service. Gradually since its establishment until now, therefore the petshop can last up to 3 years